2017
DOI: 10.5614/j.eng.technol.sci.2017.49.5.3
|View full text |Cite
|
Sign up to set email alerts
|

Crashworthiness Design for an Electric City Car against Side Pole Impact

Abstract: Abstract. Electric vehicles are increasingly popular as an alternative to fossil fuel vehicles. The presence of batteries and electric motors poses different risks in collision accidents. The deformation of the batteries could spark a fire or explosion that in turn could endanger the passengers. The prototype of an Indonesian electric city car is currently being developed, which includes a battery pack located underneath the passenger compartment and electric motors in the front compartment. A crashworthiness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Results found a significant reduction on occupant compartment acceleration when using battery packs as energy-absorption components. Setiawan and Salim [82] presented FEM model to examine the performance of energy absorbing materials for securing the battery pack against the oblique side pole crash at 32 km/h. The use of aluminum foam as a filler for the door sill structure, showed an adequate battery pack deformation of 9.4 mm compared to the 15.3 mm limit.…”
Section: Recent Research On Crashworthiness Of Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results found a significant reduction on occupant compartment acceleration when using battery packs as energy-absorption components. Setiawan and Salim [82] presented FEM model to examine the performance of energy absorbing materials for securing the battery pack against the oblique side pole crash at 32 km/h. The use of aluminum foam as a filler for the door sill structure, showed an adequate battery pack deformation of 9.4 mm compared to the 15.3 mm limit.…”
Section: Recent Research On Crashworthiness Of Evsmentioning
confidence: 99%
“…Zhang et al [83] adopted China NCAP (C NCAP) for full wrap frontal crash tests at a speed of 50 km/h. Euro NCAP side pole tests with a test speed of 29 km/h were adopted in FEM models of Roland et al [77] and Schäffer et al [80], while Setiawan and Salim [82] simulated an oblique side pole test at 32 km/h. Regarding the EVs' fire incidents reported in Table 3 and their discussion provided in paragraph 2 of Section 5, the frontal crash speeds are 71 km/h (Guangzhou, China), 97 km/h (South Jordan, USA), 120 km/h (Mountain View, California and Northern Greece), 137 km/h (Broward County, Florida), 160 km/h (West Hollywood), 177 km/h (Merida, Mexico), and 185 km/h (Fort Lauderdale, Florida).…”
mentioning
confidence: 99%
“…The area of the lower instrument panel shall provide for the possibility of parallel contact of the knees on the instrument panel in accordance with the front crash requirements. The center console also often requires modifications due to side accident regulations [4].…”
Section: The Impact Of Occupant Safety On the Interior And Exterior Of Vehiclesmentioning
confidence: 99%
“…In this context, the analysis of foams of different compositions have led to a productive research activity: aluminum foam to minimize damage to the batteries of an electric vehicle in case of collision has been applied [13], and the increase in the energy absorption capacity of Al-Cu-Mg open-cell foams by heat treatment has been studied [14]. Additionally, an open-cell nickel foam-natural rubber hybrid materials has been analyzed, and it was concluded that its compression energy absorption capacity was higher than that of open-cell nickel foam and natural rubber [15].…”
Section: Introductionmentioning
confidence: 99%
“…More applied solutions to improve the energy absorption of safety devices in vehicles can be found in Setiawan and Salim [13], who developed an impact energy absorber, based on aluminum foam to protect the batteries of an electric vehicle. An energy absorber, in the event of an impact, combined with a mechanical fuse was presented by Oyan [27].…”
Section: Introductionmentioning
confidence: 99%